9-9a+5-(-4a)-a=

Simple and best practice solution for 9-9a+5-(-4a)-a= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9-9a+5-(-4a)-a= equation:


Simplifying
9 + -9a + 5 + -1(-4a) + -1a = 0

Remove parenthesis around (-4a)
9 + -9a + 5 + -1 * -4a + -1a = 0

Multiply -1 * -4
9 + -9a + 5 + 4a + -1a = 0

Reorder the terms:
9 + 5 + -9a + 4a + -1a = 0

Combine like terms: 9 + 5 = 14
14 + -9a + 4a + -1a = 0

Combine like terms: -9a + 4a = -5a
14 + -5a + -1a = 0

Combine like terms: -5a + -1a = -6a
14 + -6a = 0

Solving
14 + -6a = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-14' to each side of the equation.
14 + -14 + -6a = 0 + -14

Combine like terms: 14 + -14 = 0
0 + -6a = 0 + -14
-6a = 0 + -14

Combine like terms: 0 + -14 = -14
-6a = -14

Divide each side by '-6'.
a = 2.333333333

Simplifying
a = 2.333333333

See similar equations:

| z/-10=8 | | (d^2+6d+9)+(d^3+6d+9)= | | 7y-2=51/2x-1/2 | | f(x)=0.125e-0.125 | | 7y-2=51/2-1/2 | | 1/3c=-1 | | -.02x^2+33x-4200=0 | | 6x+3=1x+18 | | 42=-6/5*x | | t^2/3-2t^1/3=8 | | 11=17-3k | | 7a+(10)-2a+1= | | 8y+16=4y | | -(d+22)= | | 3+3(4x-4)=9-4(2x+1) | | 8x^2(6x^3-1)= | | 10-(1/15x)=(1/10x) | | 4/5-3/5x(3/4)^-1 | | w-33/7=7 | | 8x+4+3(x+3)+2= | | 6.2/100 | | 9y=18.9 | | 2*9*4+2*4*x+2*4*x=9*4*x | | -(-2x-7y-15)= | | X+(x-24)+(x-35)=100 | | 9x-12+4x=86-2x+7 | | 4x-10x-24=0 | | X+(x-24)+(z-35)=100 | | 8+3m=17 | | 10n+4n+(-3n)+2= | | 4w-2=35 | | 3u+10=16 |

Equations solver categories